Mortality of women of fertile age in a tertiary hospital in Recife-PE: a retrospective study (2015-2019) (Research, Society and Development, 2021)
The mortality of women of childbearing age and in the puerperal period corresponds to an important portion of female deaths in the country, with maternal mortality being an important indicator to assess the quality of health care offered to the population. Hypertension, hemorrhage, puerperal infections, diseases of the circulatory system complicated by pregnancy, childbirth and the puerperium and abortion are the main causes of maternal death in the country. Therefore, the objective of this work is to describe the deaths of women of childbearing age notified at the Barão de Lucena Hospital from January 2015 to October 2019. This is a descriptive, retrospective study of a quantitative character, carried out from death notification forms and hospital records of women of childbearing age, aged 10 to 49 years who died at Hospital Barão de Lucena. The study showed a higher number of deaths among women aged 40-49 years, of brown color, low education and without a steady partner. As for the causes of death, the most prevalent was cancer and maternal deaths. Among maternal deaths, the most prevalent cause was hypertensive syndrome. We identified the need to urgently reinforce health promotion actions, disease and disease prevention, screening programs and early diagnosis, ensuring quality and resolutive services at all levels of care for all women.